2021
DOI: 10.1186/s12302-021-00479-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential influences of (±) anatoxin-a on photolocomotor behavior and gene transcription in larval zebrafish and fathead minnows

Abstract: Background Though anatoxin-a (antx-a) is a globally important cyanobacterial neurotoxin in inland waters, information on sublethal toxicological responses of aquatic organisms is limited. We examined influences of (±) antx-a (11–3490 µg/L) on photolocomotor behavioral responses and gene transcription associated with neurotoxicity, oxidative stress and hepatotoxicity, in two of the most common alternative vertebrate and fish models, Danio rerio (zebrafish) and Pimephales promelas (fathead minnow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…These studies typically require small-diameter wells and use locomotor behavior as an output for measuring toxicity. A few studies have reported significant changes in locomotion and activity levels when arena size increased, while exposure concentrations and other variables remained constant 17,27,28,39 . Another study reported significant changes in locomotion and an interaction between well size and the concentration of a neurostimulant 28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies typically require small-diameter wells and use locomotor behavior as an output for measuring toxicity. A few studies have reported significant changes in locomotion and activity levels when arena size increased, while exposure concentrations and other variables remained constant 17,27,28,39 . Another study reported significant changes in locomotion and an interaction between well size and the concentration of a neurostimulant 28 .…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported significant changes in locomotion and activity levels when arena size increased, while exposure concentrations and other variables remained constant 17,27,28,39 . Another study reported significant changes in locomotion and an interaction between well size and the concentration of a neurostimulant 28 . In these studies locomotion of larvae was tested in dim light for an extended perior 39 , or in variations of the visuomotor response (VMR) assay in which locomotion is analyzed during repeated cycles of light and dark illumination 17,27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common strategy is to calculate the average of the response variable across the entire domain, regardless of light/dark period [3][4][5]. It is also common for univariate ANOVA to be repeated twice, once for the measurements in the light periods and once for those in the dark periods [6][7][8]. Alternatively, it may be repeated several times for each individual light/dark period itself [9][10][11].…”
Section: Standard Statistical Methods Used In Pbr Studiesmentioning
confidence: 99%
“…Two studies bring information relevant for hazard assessment of selected cyanobacterial metabolites. Lovin et al [50] observed species-specific responses in two of the most common larval fish models (zebrafish and fathead minnow) after exposure to neurotoxin anatoxina, with more pronounced sublethal effects in fathead minnows at environmentally relevant concentrations. Kubickova et al [51] conducted an extensive review focused on retinoid compounds that can be also produced by cyanobacterial blooms.…”
Section: Cyanotoxinsmentioning
confidence: 99%